Current state of cytopathology residency training: a Korean national survey of pathologists - Uiju Cho; Tae Jung Kim; Wan Seop Kim; Kyo Young Lee; Hye Kyoung Yoon; Hyun Joo Choi (Korean Society of Pathologists & the Korean Society for Cytopathology, 2023)
Background Although the Korean Society for Cytopathology has developed educational goals as guidelines for cytopathology education in Korea, there is still no systematic approach to cytopathology education status for pathology residents. Furthermore, satisfaction with cytopathology education and with the outcome of the current training/educational program has not been investigated in Korea. This study aimed to obtain comprehensive data on the current state of cytopathology education for residents and evaluate education outcomes. Methods An online survey was conducted in December 2020 for the board-certified pathologists and training residents registered as members of the Korean Society for Cytopathology. The questionnaire comprised questions that investigated the current status of cytopathology at each training institution, the degree of satisfaction with the work and education related to cytopathology, outcomes of cytopathology training, and educational accomplishments. Results Of the participants surveyed, 12.3% (132/1,075) completed the questionnaire, and 36.8% (32/87) of cytopathology residents participated. The mean overall satisfaction with cytopathology education was 3.1 points (on a 1- to 5-point scale, 5: very satisfied). The most frequent suggestion among the free description format responses was to expand educational opportunities, such as online education opportunities, outside of the individual institutions. Conclusions Our results showed that cytopathology training in Korea needs further improvement. We expect that this study will inform systematic training of competent medical personnel armed with broad cytopathology knowledge and strong problem-solving abilities.